2016
DOI: 10.1149/2.1331609jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Conductivity of the CsCl–PbCl2–PbO System

Abstract: The electrical conductivity of the chloride PbCl2-CsCl (28.7–71.3 mol %) and CsCl (18.3 mol %)–PbCl2 (81.7 mol %) eutectics with the PbO additions ranging from 0.5 to 18.0 mol % was measured depending on temperature and lead oxide concentration. The electrical conductivity of the CsCl (18.3 mol %)–PbCl2 (81.7 mol %) melt is found to be two times higher than that of the CsCl (71.3 mol %)–PbCl2 (28.7 mol %) melt within the whole range of the studied lead oxide concentrations at the same temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…The measurement setup schematic is provided in a paper. 25 It was successfully used to measure the electrical conductivity of the PbCl 2 −CsCl (28.7−71.3 mol %) and CsCl (18.3 mol %)− PbCl 2 (81.7 mol %) chloride mixtures with PbO additions ranging from 0.5 to 18 mol %.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement setup schematic is provided in a paper. 25 It was successfully used to measure the electrical conductivity of the PbCl 2 −CsCl (28.7−71.3 mol %) and CsCl (18.3 mol %)− PbCl 2 (81.7 mol %) chloride mixtures with PbO additions ranging from 0.5 to 18 mol %.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Devyatkin and Kaptay analyzed the physical, chemical, and electrochemical behavior of boron oxide and its compositions with alumina in a cryolite melt, and the authors found the melt stabilization conditions. , The formation of stable forms of silicate and oxy-fluoride ionic groups was observed at the SiO 2 dissolution in an oxy-fluoride melt . Complex research on the properties and interactions between the components of the model ternary chloride CsCl–PbCl 2 –PbO system was performed earlier to determine an oxy-chloride melt structure. Lead oxide dissolubility, liquidus temperature, and thermodynamic characteristics of lead oxide dissolution in a chloride melt were determined, and an in situ Raman spectrum experiment was performed for the examination of the interaction between the oxy-chloride mixture components.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper reports on the new achievements in the development of the technology for electrochemical production of non-ferrous metals in chloride melts presented in previous papers [ 20 , 21 , 22 ]. The electric conductivity and liquidus temperature of the molten KCl–PbCl 2 [ 20 ] and CsCl–PbCl 2 [ 21 , 22 ] systems containing lead oxide have been measured.…”
Section: Introductionmentioning
confidence: 99%
“…The present paper reports on the new achievements in the development of the technology for electrochemical production of non-ferrous metals in chloride melts presented in previous papers [ 20 , 21 , 22 ]. The electric conductivity and liquidus temperature of the molten KCl–PbCl 2 [ 20 ] and CsCl–PbCl 2 [ 21 , 22 ] systems containing lead oxide have been measured. Three types of laboratory electrolytic cells for electrorefining of metallic Pb containing Sb and Bi have been developed and tested [ 23 ]: the electrolytic cell with a bipolar metallic electrode, the electrolytic cell with two anodes and one cathode, and that with a porous diaphragm.…”
Section: Introductionmentioning
confidence: 99%
“…The present work is a continuation of a series of papers on a complex study of the properties and interaction between components of the CsCl-PbCl 2 -PbO ternary chloride system, [14][15][16][17] which includes determination of lead oxide solubility in the chloride melt, liquidus temperature, thermodynamic characteristics of dissolution and performing in situ Raman experiment to detect oxychloride system components interaction.…”
mentioning
confidence: 99%